Multidrug and vancomycin-resistant Enterococcus isolates in different productive stages of a poultry farm - González, Juliana (2025)
The poultry industry represents an important economic sector in Argentina. In thisstudy we recovered 26 vancomycin-resistant Enterococcus (VRE) isolates from different productive stages of a poultry farm located in Tandil, Argentina. Ten isolates were Enterococcusfaecium and seven, Enterococcus faecalis. Total resistance to vancomycin (96.2%), erythromycin(80.8%), levofloxacin (57.7%), chloramphenicol (26.7%), penicillin (23.1%), ampicillin (7.7%) wasdetected and 20 isolates (76.9%) were identified as multidrug-resistant (MDR). With respect tothe distribution of glycopeptide resistance genes, 57.7% of the isolates harbored the vanC-1gene, and 11.5%, carried the vanC-2/C-3 gene. The vanA and vanB variants were not detected.This study provides evidence that healthy chickens from the studied region can be a reservoirof MDR---VRE. Further surveillance should be conducted to control their dissemination throughthe food chain.